NEW METHODS OF TEACHING ENGLISH IN HIGHER EDUCATION - DJUMANOVA MAKHABO RIXSIBAEVNA (International Journal of Innovations in Engineering Research and Technology, 2021)
The article discusses different ways of teaching foreign languages in universities. Particular attention was paid to the following methods: direct method, grammatical-translational, audio-visual, audio-lingual and communicative.